PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI AKUNTANSI PADA UD. ERFIN JAYA - Riyanto, Eric Jonathan; Setiawan, Alexander; Rostianingsih, Silvia (Jurnal Infra, 2014)
UD. ERFIN JAYA is a company which is engaged in distribution of building materials, with the main business serving customers who want to buy building materials. The main thing of this companys business processes is the distribution of goods and the payment from the customer on time. In day-to-day activities UD.ERFIN JAYA still in the process of implementing the manual system of recording transactions and determine profit and loss. With the manual recording system that still has a lot of risk. One risk that often occurs is the risk of human error. Therefore, with the implementation of Accounting Information Systems, then the accounting records of the company will be more structured and reduce human error which may occur.This application has the ability to manufacture the master database for suppliers, customers, goods, COA, employees, category, and units. Transactions include purchases, sales transactions, debt payments, debt payments, purchase returns, sales returns, and making of the journal automatically.Overall the application in accordance with company requirements. This application can help the owner to know the financial condition of the company through the reports produced by the program because of all the transactions made by the company are integrated with automated journal which is used as a rapid-forming materials report.